A green and convenient method for regioselective mono and multiple benzoylation of diols and polyols. Issue 7 (18th February 2016) - Zhang, Xiaoling; Ren, Bo; Ge, Jiantao; Pei, Zhichao; Dong, Hai
Abstract: An efficient method for regioselective benzoylation of diols and polyols was developed. The benzoylation is catalyzed by only 0.2 equiv of benzoate anion in acetonitrile with the addition of a stoichiometric amount of benzoic anhydride under very mild condition, leading to high yields. Compared with all other methods, this method shows particular advantage in regioselective multiple benzoylation of polyols, and in avoiding the use of any metal-based catalysts and any amine bases, which is more environment-friendly. Graphical abstract: